Curriculum Development in Higher Education - from Theory to Practice at VNU University of Education in the Context of University Autonomy Implementation - Yen, Duong Thi Hoang; Huyen, Nguyen Phuong; Ly, Nguyen Thanh; Duong, Nghiem Thi (VNU Journal of Science: Education Research; Vol 35 No 4DO - 10.25073/2588-1159/vnuer.4309, 2019)
In the trend of innovation and autonomy in higher education, curriculum development plays an important role for each university to affirm its quality and position. This paper argues that a new meaning for undergraduate curriculum must be developed to reflect the University's autonomy and ensure its efficiency. This requires renewed discussion of all aspects of curriculum in higher education, from theory to practice. This paper also discusses the result of a study on the curriculum development in the University of Education (UED) - a member university of Vietnam National University, Hanoi (VNU), assesses the degree of autonomy and effectiveness of the curriculum as well as proposes solutions to ensure the quality of training, realizing the vision and mission of the University.